Effects of some epidemiological factors on levels of disease caused by Dactylaria higginsii on Cyperus rotundus - Kadir, J.B.; Charudattan, R.; Berger, R.D. (BioOne, 2000)
The objective of this study was to identify some epidemiological conditions that affect the pathogenicity and weed control efficacy of the fungal pathogen Dactylaria higginsii on Cyperus rotundus. In controlled environments, the fungus required a minimum dew period of 12 h and a temperature of 25 C during the dew period to produce severe disease on four- and six-leaf-stage plants inoculated with 106 conidia ml-1. Under these conditions, 75% disease (percent leaf area damaged) and excellent weed control (nearly 100% plant mortality) were achieved. In experiments to test the interaction among dew period temperature, dew period duration, and plant growth stages, younger plants (four- to six-leaf) were more susceptible to D. higginsii than older (eight-leaf-stage) plants. At the dew period duration of 24 h and dew period temperature of 30 C, the number of days to obtain 50% disease severity on four- to six-leaf-stage plants was significantly less (10 d) compared with older plants (16 d). To achieve effective control, D. higginsii should be applied early in the growing season when C. rotundus plants are young and the temperature and dew period requirements are not limiting. The need for a long dew period (> 12 h) for infection and disease development may be a limiting factor in this pathosystem. This limitation may be overcome by using inoculum amended with moisture-retaining gels.